Prognosis for Young Females with Pseudomyxoma Peritonei of Appendiceal Origin and Unilateral or Bilateral Ovaries Preserved During Cytoreductive Surgery - Fu, Fengxian; Tang, Huangdong; Lu, Yiyan; Lu, Dongmei; Ma, Ruiqing (Frontiers in Surgery, 2022)
Objective: To determine prognosis for young female patients with peritoneal pseudomyxoma (PMP) of appendiceal origin and unilateral or bilateral ovaries preserved during cytoreductive surgery (CRS). Methods: Clinical data of female patients treated with CRS with or without hyperthermic intraperitoneal chemotherapy (HIPEC) at the Aerospace Center Hospital, Beijing between January, 2009 and December, 2019 were retrospectively reviewed. The demographic and clinical characteristics and prognosis of women with ovaries preserved (ovarian preservation group) or resected (ovarian resection group) during CRS were compared. Independent prognostic factors for survival were identified using univariate and multivariate analysis. Results: 40 patients were included in the final analysis. 19 patients chose ovarian preservation while 21 patients underwent ovarian resection. Completeness of cytoreduction (CCR) scores were CCR-0/1. There were significant differences in age (<40 vs. ≥40), symptoms, intraoperative HIPEC (Y vs. N), and histopathologic subtype of PMP (low-grade vs. high-grade) (P<0.001) between patients in the ovarian preservation and ovarian resection groups. In the ovarian preservation group, median overall survival (OS) was 59 months (range, 53 to 65 months), and the 5-year survival rate was 37.9%. Median disease-free survival (DFS) was 13 months (range, 9 to 17 months), and the 5-year recurrence rate was 87.4%. In the ovarian resection group, the 5-year survival rate was 87.7%, and the 5-year recurrence rate was 18.3%. Median OS and median DFS were not reached. In patients with low-grade PMP, median DFS was significantly longer in patients with ovarian resection compared to ovarian preservation (P<0.001). Univariate analysis showed histopathologic subtype of PMP (low-grade vs. high-grade, P<0.001) was significantly associated with OS and DFS. On multivariate analysis, high-grade histopathologic subtype of PMP was an independent predictor of poor prognosis (OS and DFS). Conclusion: Histopathologic subtype of PMP represents an independent predictor of prognosis in female patients with PMP of appendiceal origin and unilateral or bilateral ovaries preserved during CRS. These findings imply that ovarian preservation is a more suitable option for young females with low-grade PMP compared to high-grade PMP. Further prospective studies should be done investigating the role of resection of uninvolved ovaries in PMP.